High phosphate impairs arterial endothelial function through AMPK‐related pathways in mouse resistance arteries. (20th December 2020) - Hu, Weipeng; Jiang, Shan; Liao, Yixin; Li, Jinhong; Dong, Fang; Guo, Jie; Wang, Xiaohua; Fei, Lingyan; Cui, Yu; Ren, Xiaoqiu; Xu, Nan; Zhao, Liang; et al.
Abstract: Aims: In patients with renal disease, high serum phosphate shows a relationship with cardiovascular risk. We speculate that high phosphate (HP) impairs arterial vasodilation via the endothelium and explore potential underlying mechanisms. Methods: Isolated vessel relaxation, endothelial function, glomerular filtration rate (GFR), oxidative stress status and protein expression were assessed in HP diet mice. Mitochondrial function and protein expression were assessed in HP‐treated human umbilical vein endothelial cells (HUVECs). Results: High phosphate (1.3%) diet for 12 weeks impaired endothelium‐dependent relaxation in mesenteric arteries, kidney interlobar arteries and afferent arterioles; reduced GFR and the blood pressure responses to acute administration of acetylcholine. The PPARα/LKB1/AMPK/eNOS pathway was attenuated in the endothelium of mesenteric arteries from HP diet mice. The observed vasodilatory impairment of mesenteric arteries was ameliorated by PPARα agonist WY‐14643. The phosphate transporter PiT‐1 knockdown prevented HP‐mediated suppression of eNOS activity by impeding phosphorus influx in HUVECs. Endothelium cytoplasmic and mitochondrial reactive oxygen species (ROS) were increased in HP diet mice. Moreover HP decreased the expression of mitochondrial‐related antioxidant genes. Finally, mitochondrial membrane potential and PGC‐1α expression were reduced by HP treatment in HUVECs, which was partly restored by AMPKα agonist. Conclusions: HP impairs endothelial function by reducing NO bioavailability via decreasing eNOS activity and increasing mitochondrial ROS, in which the AMPK‐related signalling pathways may play a key role.